Phosphine catalyzed δ-carbon addition and isomerization of alkynones to ketimines: the preparation of 1, 3-diene substituted dihydroquinazolinones and 3-aminooxindoles. Issue 2 (12th October 2017) - Sun, Yao-Liang; Wei, Yin; Shi, Min
Abstract : A novel strategy of the phosphine catalyzed addition of alkynones to ketimines for the synthesis of α-amino diene derivatives has been developed for the first time, thus providing diene incorporating α-amino products in moderate to excellent yields. Abstract : In this paper, we disclosed that alkynones could be activated as nucleophilic synthons of dienes to smoothly react with several ketimines upon phosphine catalysis, providing three kinds of α-amino diene derivatives in moderate to excellent yields. A plausible mechanism has been proposed on the basis of control experiments. Transformations of 3, 5-dien-2-one derivatives were also performed to provide diverse polyene products.